MOTIVASI WANITA USIA REPRODUKSI SEHAT ( 20-35 TAHUN ) PADA PEMILIHAN KB IUD PASCA PLACENTA - Ratnaningsih, Tri; Rosalia, (JURNAL KEPERAWATAN BINA SEHAT, 2015)
KB (family planning) Post Placenta is supply to KB (family planning) for patient who has childbirth till the time as long as 42days. The woman’s reproduction health age (20-35 yearsold) is an reproduction woman which has organ. Fisiology and pshychology optimily have not reached to emotion and spirituation is adult enough as like this women has a good reproduction organ so make a pregnancy faster. Support from family and her husband is more important to shoose a good KB (family planning) specifically. IUD,s family planning (KB) Post Placenta. The purpose for this research is to know the motivation of health reproduction woman age (20-35). Kind ofthis research is descriptive research included by population 278 person following woman,s health reproduction age in Blimbing city. Sooko. Mojokerto on july 2015. The sampling technical is used to purposive sampling. The data was taken by used questionaire and next to scorrying with likest skala most of this result is showed that a good reproduction women age. Are 119 respondent who has motivation enought 76 person (63,3 percent). They need a motivation to choose KB accuratelly to thread cancel and spase for her pregnancy and look foor more information about KB for the one. Mother and ungood news. Hopefully most all the husband help their wife to give information and motivation to choose a good KB specific for IUD pasca placenta.Keyword : Motivation,Healthy Women Reproductive Age,IUDPostPlacentaKB (Family Planning)